The identity thief collection - Mulraney, Peter ([Victor Harbor, South Australia] : Peter Mulraney, 2018)
"The Identity Thief: Detective Sergeant Stella Bruno investigates the murder of 'nice guy' Bob Cunningham, and discovers he wasn’t who he claimed to be. To solve this one, Stella not only has to work out who the victim was, she also needs to find out why he was pretending to be someone else. And, there’s the distraction of Shaun Porter, the new man from Public Prosecutions, who walks into her life. A Gun of Many Parts: Easy to use and conceal, Glock pistols are the weapon of choice in the Australian criminal underworld, even though possession of a Glock is restricted under Australian law. When a Glock with multiple serial numbers is discovered in the wreckage of a car after a senseless shooting, Detective Sergeant Stella Bruno investigates and finds herself on the trail of a group of gun smugglers making creative use of a Licensed Post Office. Bones in the Forest: A skeleton, found after a fire in Wirrabara Forest, is identified as a young man reported missing five years before the fire. Detective Sergeant Stella Bruno investigates. The trail is cold. The evidence is circumstantial. Stella wonders if they'll find a way to solve the case. Detective Constable Brian Rhodes has his own ideas on this one. If you enjoy mystery and intrigue, you'll love this collection of Peter Mulraney's quick reads" -- cover description.
"This edition published 2018" -- title page verso.
"Three Stella Bruno investigates stories" -- cover description.
Keywords: Detective and mystery stories, Australian; Short stories, Australian -- 21st century; Australian fiction -- 21st century; Australian